A FLOUTING MAXIMS ANALYSIS IN THE MOVIE ENTITLED “HARRY POTTER AND THE PHILOSOPHER’S STONE” (PRAGMATICS APPROACH) - Ika Oktaria Cahyaningrum; Nilam Agustin (Musamus Journal of Language and Literature, 2020)
This research was conducted to describe the kinds of flouting maxims employed by the characters in the movie entitled “Harry Potter and the Philosopher’s Stone” and to explain the purpose or reasons of the characters in the film flouted maxims in their dialogue and utterances. This analysis will use descriptive qualitative and total sampling technique. The data of this research are the dialogues containing maxims that were uttered by the characters in the movie. The data are classified based on Grice’s Theory of Flouting Maxims. Technique of collecting data is documentation. Technique of analyzing data is Referential Identity Method and Triangulation for validation of the data. The researcher found there are four types of flouting maxims. Totally, there are 62 data conducted maxims such as 9 data Maxims of Quality (14,51%), 19 data of Maxims of Quantity (30,64%), 16 data Maxims of Relevance (25,80%) and 18 data Maxims of Manner (29,05%). Secondly, the reasons of the characters in the movie in employing flouting maxims in their dialogues are: privacy and profession reason used to flout Maxims of Quality; confirmation and refusal reason used to flout Maxims of Quantity; safety, education, anger and privacy reason used to flout Maxims of Relevance; empathy, and humor reason used to flout Maxims of Manner.